Land Tenure Security and Sustainable Development - Holland, Margaret B.; Masuda, Yuta J.; Robinson, Brian E. (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book presents a nuanced and accessible synthesis of the relationship between land tenure security and sustainable development. Contributing authors have collectively worked for decades on land tenure as connected with conservation and development across all major regions of the globe. The first section of this volume is intended as a standalone primer on land tenure security and its connections with sustainable development. The book then explores key thematic challenges that interact directly with land tenure security, followed by a section on strategies for addressing tenure insecurity. The book concludes with a section on new frontiers in research, policy, and action. An invaluable reference for researchers in the field and for practitioners looking for a comprehensive overview of this important topic. Margaret B. Holland, PhD, Associate Professor, Department of Geography & Environmental Systems, University of Maryland, Baltimore County. Yuta J. Masuda, PhD, Senior Sustainability and Behavioral Scientist, The Nature Conservancy. Brian E. Robinson, PhD, Associate Professor, Department of Geography, McGill University.